2018
DOI: 10.1249/jsr.0000000000000533
|View full text |Cite
|
Sign up to set email alerts
|

Returning to Sport After Gymnastics Injuries

Abstract: Acute and overuse injuries are a common experience for artistic gymnasts; however, this population has unique needs when returning to their sport after an injury due to the technical demands imposed during gymnastics. We reviewed the current literature regarding return to play (RTP) in artistic gymnasts and developed four goals: 1) to define the guiding principles used to determine RTP in sports, 2) to identify factors that affect recovery progression among gymnasts, 3) to determine how different injury types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…18,19 While there are promising new chemical interventions to halt the progression of mitochondrial and other biochemical processes, 20,21 the current standard of care is to prescribe rehabilitation therapy to improve supporting musculature strength, joint functionality, and decrease pain. [22][23][24] It is unknown, however, if movement soon after joint injury is beneficial or detrimental to long-term outcome and the development of PTOA. Complete immobilization of knee joints has been noted to be beneficial for up to 2 weeks post-surgery by decreasing rate of apoptosis and increasing rate of proliferation.…”
mentioning
confidence: 99%
“…18,19 While there are promising new chemical interventions to halt the progression of mitochondrial and other biochemical processes, 20,21 the current standard of care is to prescribe rehabilitation therapy to improve supporting musculature strength, joint functionality, and decrease pain. [22][23][24] It is unknown, however, if movement soon after joint injury is beneficial or detrimental to long-term outcome and the development of PTOA. Complete immobilization of knee joints has been noted to be beneficial for up to 2 weeks post-surgery by decreasing rate of apoptosis and increasing rate of proliferation.…”
mentioning
confidence: 99%
“…Progressive planning of the type, content and progression of training loads also relevant to minimise injury risk and optimise performance (Zetaruk et al, 2006). The volume of repetitions and adequate recovery time, as well as nutritional and psychological health, should be taken consideration for managing successful progressive return to sport following injury (Sweeney et al, 2018). Therefore, medical providers should encourage clear and open communication between the athlete, coach and medical team to keep the athlete healthy (Sweeney et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The volume of repetitions and adequate recovery time, as well as nutritional and psychological health, should be taken consideration for managing successful progressive return to sport following injury (Sweeney et al, 2018). Therefore, medical providers should encourage clear and open communication between the athlete, coach and medical team to keep the athlete healthy (Sweeney et al, 2018). Depending on the level of injury, it may take more time for the athlete to improve her performance and reach a good technical level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Serner et al (2020) concluded that soccer players who successfully completed criteria-based exercise testing to define the end of their basic rehabilitation (recovery) phase prior to starting the functional (RTS/late rehabilitation) phase, had a significantly lower re-injury rate than athletes who did not [25]. However, the available protocols directing when to start sports-specific movements are not specific to ballet [5][6][7][8][9][10]18,23,25,26,[45][46][47][48][49][50]. For ballet dancers returning from injury, there is a need for validated criteria to determine when a ballet dancer is ready to begin RTS and protocols to safely direct the dancer to full participation.…”
Section: Table 3: Common Ballet Injuries and Ballet Specific Consider...mentioning
confidence: 99%
“…A ballet-specific RTS protocol allows the dancer to prepare for the sport's specific demands in order to maximize safe re-entry into ballet and to decrease re-injury rates [6,51]. As our literature review did not uncover any body region-specific, validated return to ballet protocols, the progressive stages of our protocol were created based on the review of the general sports medicine literature, knowledge of the biomechanical principles of ballet skills, review of expert opinions, and our extensive clinical experience [5,[8][9][10]14,15,25].…”
Section: Table 3: Common Ballet Injuries and Ballet Specific Consider...mentioning
confidence: 99%